A Study of Knitted Fabric from Thai Silk Waste Yarn - Peeraya Sramala (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
Thai silk is a part of Thailand regional cultural heritage. The unique characteristics are gummy, sticky substance and shining. Thai silk Industry share a common problem to other industries, the process produces a lot of waste. A solid waste from Thai silk can be classified into three types: Incomplete cocoons broken silk yarn; and silk fabric waste. Generally, these waste use for reuse in the business roles such as fashion accessories and decorative produc t. In order to adding value to Thai Silk waste can be done by knitted fabric properties: more flexible and able to produce in flat, seamless, and three dimension. The recycle concept led to following studies: 1) To do an experiment of yarn spinning from Thai silk waste fibre; 2) To experiment a knitted fabric from a yarn of Thai silk waste and; 3) To experiment yarn dyed and knitted fabric piece dyed by natural dyeing colour. A method of study consist of fibre preparing and spinning by hand, the equipment to develop knitted fabric are hand knitting and knitting machine, the natural dyeing colour come from coffee grounds, Turmeric, Red cabbage, and Mulberry. The result of study are: 1) Fibre and spinning experiment shown a yarn is uneven; yarn from broken silk yarn, silk fabric waste, and incomplete cocoon fibre are sticky and softly touch respectively; 2) Knitted fabric experiment showed that the production by hand knitting are soft and flexible than a knitting machine. While knitting machine fabric is smooth surface than hand knitting fabric and; 3) Natural colour dyeing experiment showed that the colour absorption of yarn dyed is better than piece dyed. In conclusion, a result of the study can be used as a guideline idea to create new knitted fabric made from Thai silk waste to present the aesthetic values through textures, colours, structure and pattern.